On the structure and function of plant K+ channels - Hedrich, Rainer; Hoth, Stefan; Becker, Dirk; Dreyer, Ingo; Dietrich, Petra (1998)
Patch clamp studies have identified K+ uptake and K+ release channels, two major channel types which are inversely activated by the membrane voltage (Blatt, 1988, 1992; Schroeder, 1988, 1989; for review see Schroeder et al., 1994; Hedrich and Dietrich, 1996). Besides, voltage-independent cation channels with often very broad selectivity were described as well (Hedrich and Neher; 1987; Enz et al., 1993; Schuiz-Lessdorf and Hedrich, 1995;Allen and Sanders, 1996). Since for K+ uptake and K+ release channels extensive in vivo-studies, molecular cloning and functional expression analyses are available this review will focus on these channel types, only.
Keywords: K+ channel; plant physiology; heterologous expression; cation sensitivity